2013
DOI: 10.4103/1596-3519.112414
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity using GHQ-28 among cleft lip patients in Sokoto

Abstract: In addition to reconstructive surgery, psychiatric evaluation and intervention would be of benefit in the management of cleft lip patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Major Depressive Disorder was also found to be significantly more prevalent in individuals with CL/P than in controls (Demir et al, 2011). The prevalence of psychiatric morbidity was 28.5% among patients with CL/P in one study, which was found to be significantly higher than the control group (Yunusa & Obembe, 2013). However, the rate of psychiatric diagnoses was not found to differ significantly from the general population in another study (Shriver et al, 2006).…”
Section: Emotional Wellbeingmentioning
confidence: 83%
“…Major Depressive Disorder was also found to be significantly more prevalent in individuals with CL/P than in controls (Demir et al, 2011). The prevalence of psychiatric morbidity was 28.5% among patients with CL/P in one study, which was found to be significantly higher than the control group (Yunusa & Obembe, 2013). However, the rate of psychiatric diagnoses was not found to differ significantly from the general population in another study (Shriver et al, 2006).…”
Section: Emotional Wellbeingmentioning
confidence: 83%
“…However, general societal neglect for cleft palate can lead to decreased access to palatal surgery [56, 61], and furthermore, CP has implications for feeding, speech and jaw development and is usually associated with syndromes. This type of cleft is more likely to increase morbidity and mortality from poor feeding leading to child malnutrition and vulnerability to infectious diseases [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…The possible sequelae of undetected hearing loss can be socially isolating and compound challenges with communication. Another problem of clefts of the lip (CL) is the physical deformity and the associated social and psychiatric morbidity [2,3]. The stigma of an unrepaired orofacial cleft greatly alters a child’s ability to integrate into the social and cultural environment.…”
Section: Introductionmentioning
confidence: 99%